Characterization of a Complex Mixture of Immunomodulator Peptides Obtained from Autologous Urine - Alberto Fragoso; Mérida Pedraza-Jiménez; Laura Espinoza-González; María Luisa Ceja-Mendoza; Hugo Sánchez-Mercado; Gloria Robles-Pérez; Julio Granados; Emilio Medina-Rivero (Journal of Immunology Research)
A complex mixture of peptides plays a key role in the regulation of the immune system; different sources as raw materials mainly from animals and vegetables have been reported to provide these extracts. The batch-to-batch product consistency depends on in-process controls established. However, when an immunomodulator is a customized product obtained from the same volunteer who will receive the product to personalize the treatment, the criteria to establish the consistency between volunteers are different. In this sense, it is expected to have the same molecular weight range although the profile of peptide abundance is different. Here, we characterized the peptide profile of three extracts of an immunomodulator obtained from the urine of different volunteers suffering from three different diseases (i.e., allergic rhinitis, rheumatoid arthritis, and chronic rhinopharyngitis), using size exclusion chromatography (SEC) and mass spectrometry (MS). The peptides contained in the immunomodulators were stable after six months, stored in a refrigerator. Our results showed a chromatographic profile with the same range of low molecular weight (less than 17 kDa) in all analyzed samples by SEC; these results were also confirmed by MS showing an exact mass spectrum from 3 to 13 kDa. The fact that the peptide profiles were conserved during a six-month period at refrigeration conditions (2 to 8°C) maintaining the quality and stability of the immunomodulator supports the notion that it might be an alternative in the treatment of chronic hypersensibility disorders.